2009
DOI: 10.1038/onc.2009.277
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic proapoptotic effects of the two tyrosine kinase inhibitors pazopanib and lapatinib on multiple carcinoma cell lines

Abstract: Pazopanib and lapatinib are two tyrosine kinase inhibitors that have been designed to inhibit the VEGF tyrosine kinase receptors 1, 2 and 3 (pazopanib), and the HER1 and HER2 receptors in a dual manner (lapatinib). Pazopanib has also been reported to mediate inhibitory effect on a selected panel of additional tyrosine kinases such as PDGFR and c-kit. Here, we report that pazopanib and lapatinib act synergistically to induce apoptosis of A549 non-small-cell lung cancer cells. Systematic assessment of the kinome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 64 publications
1
43
0
1
Order By: Relevance
“…48 As an example, the combination of several tyrosine kinase inhibitors with different specificities, as well as elevated concentrations of a single compound, reportedly lead to a rapid collapse of the tyrosine kinase network, resulting in efficient cell killing. 49 What are the mechanisms through which the inactivation of p53 augments the susceptibility of cancer cells to the cytotoxic effects of high-dose reversine? Based on our observations, it is tempting to hypothesize that the preferential cytotoxicity of high-dose reversine for p53-deficient cells might be intimately linked to specific cell cycle aberrations, in turn resulting from the deregulation of cell cycle checkpoints.…”
Section: Methodsmentioning
confidence: 99%
“…48 As an example, the combination of several tyrosine kinase inhibitors with different specificities, as well as elevated concentrations of a single compound, reportedly lead to a rapid collapse of the tyrosine kinase network, resulting in efficient cell killing. 49 What are the mechanisms through which the inactivation of p53 augments the susceptibility of cancer cells to the cytotoxic effects of high-dose reversine? Based on our observations, it is tempting to hypothesize that the preferential cytotoxicity of high-dose reversine for p53-deficient cells might be intimately linked to specific cell cycle aberrations, in turn resulting from the deregulation of cell cycle checkpoints.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13] We therefore first asked whether pazopanib can act directly to inhibit the proliferation of synovial sarcoma cells. As shown in Figure 1A, pazopanib showed dose-dependent growth inhibition in all synovial sarcoma cell lines examined in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Although pazopanib has been developed and is currently being clinically used as an anti-angiogenesis agent, 8,20 direct antitumor effects of pazopanib have been described in the published literature for several tumor cells, including, multiple myeloma, 10 HER2 þ breast cancer, 11 lung cancer, 12 and chronic lymphocytic leukemia cells. 13 The dose-effectiveness of pazopanib against synovial sarcoma cells in the present study was comparable to the results of these studies which showed an IC 50 value ranging between approximately 2 and 15 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…For example: the FLT3 kinase, which is related to acute myeloid leukemia, phosphorylates Tyr-containing substrate peptides found by a peptide array screening 6 . The inhibitory properties of the tyrosine kinase inhibitors pazopanib and lapatinib was tested using peptide array screening 23 . Peptides array can be used to identify the sites that mediate protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%